Remote Education in Modern University: Potential Opportunities, Quality or Availability? - Ovsyanik, Alexander I. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of this article is the need to study the development of a single information space of educational industries, the role of information and social technologies in higher professional education. It is not new for modernity, characterized by mass Informatization, digitalization and computerization, that information and communication technologies develop various spheres of human activity, including in the educational sphere. Leading universities in the world are actively using new technologies, and distance education in particular, to increase their share in the market of educational services. The purpose of the study is to identify the attitude of the teaching staff to remote educational services. Research methods: to study the attitude to distance education, we used a survey method that allows us to more thoroughly analyze the interest of the teaching staff in implementing appropriate technical support and innovative ways of presenting material. Results of the research: the article considers the readiness of the teaching staff to participate in distance learning, including as students. The experience of developing distance education courses by teachers is analyzed. It is shown that the vast majority of teachers are ready for this kind of activity. It is revealed that more than half of young teachers are the initiators of creating distance education courses, but they need to stimulate work and psychological support. It is determined that among the problems faced by teachers when developing their own distance education courses, the following were named: the lack of visual contact with students who are attendants of the courses; the difficulty of communicating only with a video camera; the lack of appropriate technical equipment. It is revealed that the University management is more interested in introducing innovative ways of presenting educational material than teachers, since this affects the status of the institution and, as a result, attracts a greater number of potential students. The authors analyze the factors that limit the readiness to create distance courses, among the most significant they identified lack of motivation and lack of time; lack of methods and material remuneration that compensates for time and intellectual costs. It is determined that social networks are rarely used for training (there is no need, no time, and no confidence in the protection of information). It is shown that the vast majority of teachers believe that distance learning has good prospects, but only if traditional education is maintained and used in a comprehensive manner, which will compensate for the shortcomings of the first and expand the opportunities of the second.